2016
DOI: 10.1136/bcr-2016-214348
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine lower extremity gangrene in a newborn with Tetralogy of Fallot

Abstract: DESCRIPTIONIntrauterine gangrene of an extremity is a rare problem. Lower extremity gangrene is even rarer. 1 We present a case of lower extremity gangrene in combination with Tetralogy of Fallot (TOF) and postaxial polydactyly of the hand. A live male infant was delivered by caesarean section. Delivery occurred at the 34th week of gestation due to meconium aspiration and intrauterine growth retardation. The mother was 35 years of age and had three healthy children. She had been diagnosed with gestational hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…[4] Seker et al reported a premature infant with tetralogy of Fallot who had lower extremity gangrene at birth. [1] In our case, the only possible risk factor was maternal gestational hypertension. Management of intrauterine gangrene includes maintenance of hemostasis, thrombolytic agents and anticoagulants, prevention of infection, and amputation when necessary.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…[4] Seker et al reported a premature infant with tetralogy of Fallot who had lower extremity gangrene at birth. [1] In our case, the only possible risk factor was maternal gestational hypertension. Management of intrauterine gangrene includes maintenance of hemostasis, thrombolytic agents and anticoagulants, prevention of infection, and amputation when necessary.…”
mentioning
confidence: 53%
“…Management of intrauterine gangrene includes maintenance of hemostasis, thrombolytic agents and anticoagulants, prevention of infection, and amputation when necessary. [1,5] Timely intervention can significantly improve the patient's outcomes.…”
mentioning
confidence: 99%